2011
DOI: 10.1111/j.1744-7917.2011.01447.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reference genes for gene expression studies in the emerald ash borer (Agrilus planipennis)

Abstract: The Emerald ash borer (EAB, Agrilus planipennis Fairmaire) an exotic invasive insect pest has killed millions of ash trees (Fraxinus spp.) across North America and threatens billions more. We validated six A. planipennis reference genes (actin, ACT; beta tubulin, β‐TUB; glyceraldehyde‐3‐phosphate dehydrogenase, GAPDH; ribosomal protein, RPL7; translation elongation factor 1α, TEF‐1α; and ubiquitin, UBQ) using geNorm, Normfinder and BestKeeper for accurate determination of target messenger RNA levels in gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…The act gene exhibited high variation in expression among different castes and tissues with P  = 0.002 and P <0.001, respectively. These results are in accordance with several studies demonstrating act gene as an unsuitable internal control for RT-PCR in other cell types or species [40], [44]. Recent studies have shown that β-act (one of the three main groups of act isoform, α, β and γ) expression can change in response to variety of conditions [45].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The act gene exhibited high variation in expression among different castes and tissues with P  = 0.002 and P <0.001, respectively. These results are in accordance with several studies demonstrating act gene as an unsuitable internal control for RT-PCR in other cell types or species [40], [44]. Recent studies have shown that β-act (one of the three main groups of act isoform, α, β and γ) expression can change in response to variety of conditions [45].…”
Section: Discussionsupporting
confidence: 92%
“…Based on the rankings from RefFinder, which integrates outcomes of three major statistic algorithms (geNorm, Normfinder and Bestkeeper) and assigns an appropriate weight to an individual gene and calculates the geometric mean of their weight, rpl18 and ef1-beta genes had a good performance under specific conditions. Moreover, ef1 (including ef1-alpha and ef1-beta ) had also been proved to be the best candidate reference gene for normalization in emerald ash borer [40], triatomines [41], bed bug [6] and honey bee [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, ACT was one of the least stable genes, in both non-infected and infected plants. The expression instability of ACT under specific conditions has been reported in other studies (Guénin et al, 2009;Huis et al, 2010;Rajarapu et al, 2012). Tubulin has also been shown to be unstable in some Citrus genotypes (Yan et al, 2012), during the developmental stages of flax (Huis et al, 2010), and in Orobanche ramosa (González-Verdejo et al, 2008).…”
Section: Discussionsupporting
confidence: 64%
“…The curve consisted of 5-fold dilutions over four points. An elongation factor 1-α ( Ap EF-1 α) was used as internal control gene, which showed stable expression in A. planipennis [111]. Fold change in gene expression among male and female antennal samples of A. planipennis were derived by the 2 −δδC T method by taking newly eclosed virgin samples (male and female) as calibrator [112].…”
Section: Methodsmentioning
confidence: 99%